An analysis of internal control systems and their influence on financial sustainability of selected institutions of higher learning in Tanzania - Sunday, Arthur; Mabonga, Eric; Tumwebaze, Lydia; Kirabo Kyeyune, Joseph B. (International Journal of Research, 2018)
The study investigated and sought to establish the relationship between internal control systems and financial sustainability in an Institution of higher learning in Tanzania. Internal controls were looked at from the perspective of Control Environment, Internal Audit and Control Activities whereas Financial sustainability focused on Liquidity, Accountability and Reporting as the measures of Financial sustainability. The Researcher set out to establish the causes of persistent poor financial sustainability from the perspective of internal controls. The research was conducted using both quantitative and qualitative approaches using Survey, Correlation and Case study as Research Designs. Data was collected using Questionnaires and Interview guide as well as review of availablefinancial reports, documents and records of the selected institutions .The study found that management of most institutions is committed to the control systems, actively participates in monitoring and supervision of the activities of the Institutions of higher leraning , all the activities of the Institution’s activities are
Keywords: Internal Control Systems; Financial Sustainability